A non-wax absorbing pad with gradient pore structure and a preparation method thereof
Patent Information
- Application Number
- CN202611386119.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-09-08
- Publication Date
- 2026-10-16
AI Technical Summary
[0006]针对现有技术中无蜡吸附垫对晶片厚度控制不够精准的技术问题,本发明提供一种具有梯度孔结构的无蜡吸附垫及其制备方法
(1)通过沿厚度方向孔径逐渐增大的梯度孔结构,实现了表层微孔均匀吸附与底层大孔高效负压传导的功能协同,显著提高了晶片在抛光过程中的固定稳定性,降低了因吸附不均导致的晶片微位移,从而改善晶片厚度均匀性;
Smart Images

Figure CN122935210A_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of chemical mechanical polishing technology, and more specifically, to a wax-free adsorption pad for fixing wafers during wafer polishing and its preparation method. Background Technology
[0002] Chemical mechanical polishing (CMP) is a key process in semiconductor manufacturing for achieving global wafer planarization. During CMP, the wafer needs to be securely fixed to the polishing head. Traditional methods include wax bonding and vacuum adsorption. Wax bonding suffers from problems such as wax residue contamination, complex dewaxing processes, and easy chipping at wafer edges. Therefore, wax-free adsorption pads have gradually become the mainstream technology.
[0003] Wax-free adsorption pads are typically made of porous polymer materials such as polyurethane and silicone rubber, and are used to adsorb and fix wafers using vacuum negative pressure. Most commercially available and patent-disclosed wax-free adsorption pads currently employ a uniform pore structure, meaning the overall pore size distribution is relatively uniform. However, in practical applications, it has been found that this uniform pore structure struggles to simultaneously meet the requirements of uniform adsorption force distribution on the adsorption surface and efficient negative pressure conduction. If the surface pore size is small, although it is beneficial for uniform adsorption force distribution, the negative pressure conduction resistance is high, the response speed is slow, and the adsorption stability is insufficient. If the surface pore size is large, the negative pressure conduction efficiency is improved, but the adsorption force distribution is uneven, resulting in uneven stress on the wafer in certain areas. This can easily lead to micro-displacement during polishing, thus affecting the wafer thickness uniformity (TTV, LTV, etc.). As semiconductor process nodes continue to shrink, the requirements for wafer thickness control precision in CMP processes are becoming increasingly stringent, and the aforementioned contradiction has become a significant factor restricting yield.
[0004] In existing technologies, improvements to wax-free adsorption pads mainly focus on the structure of the bearing head, the bonding process, or the bonding of composite layers, with less attention paid to the pore structure design of the adsorption pad material itself. For example, Chinese patent CN115056045B proposes a wafer single-sided polishing device, which improves the service life of the adsorption pad under high pressure by setting an adhesive layer and a limiting ring, but the adsorption layer itself still adopts a traditional uniform pore structure and does not involve the design of pore size gradient distribution; patent CN207757470U proposes a wax-free polishing adsorption pad bonding device, mainly solving the problem of mechanization of the bonding process, but similarly does not optimize the pore structure of the adsorption pad. Although the above-mentioned improvement schemes alleviate the mechanical performance or installation process problems of the adsorption pad to a certain extent, they do not fundamentally solve the contradiction between adsorption uniformity and negative pressure conduction efficiency in a uniform pore structure.
[0005] Therefore, how to redesign the pore structure of the wax-free adsorption pad so that the surface layer of the adsorption pad can provide uniform adsorption force while the bottom layer can efficiently conduct negative pressure, thereby improving the uniformity of wafer thickness, remains a technical problem that needs to be solved in this field. Summary of the Invention
[0006] To address the technical problem of insufficient precision in controlling wafer thickness in existing wax-free adsorption pads, this invention provides a wax-free adsorption pad with a gradient pore structure and its preparation method. By designing a gradient pore structure with gradually increasing pore size along the thickness direction, the surface micropores and the bottom macropores are functionally differentiated, achieving synergistic optimization of uniform adsorption force distribution and efficient negative pressure conduction.
[0007] To achieve the above-mentioned technical objectives, in a first aspect, the present invention provides a wax-free adsorption pad with a gradient pore structure, employing the following technical solution: A wax-free adsorption pad with a gradient pore structure has a gradient pore structure with increasing pore size along the thickness direction. The gradient pore structure includes a microporous layer located on the wafer contact side and a macroporous layer located on the negative pressure access side. The microporous layer is used to uniformly distribute the adsorption force on the adsorption surface, and the macroporous layer is used to conduct negative pressure. The gradient pore structure enables precise control of wafer thickness during the polishing process.
[0008] This invention employs a gradient aperture structure to functionally differentiate between the microporous layer on the wafer contact side and the macroporous layer on the negative pressure access side: the microporous layer, through its fine channels, forms a uniform adsorption force on the adsorption surface, preventing localized stress concentration on the wafer; the macroporous layer, with its larger pore size, reduces the resistance to negative pressure conduction, achieving rapid negative pressure response and uniform distribution. The synergistic effect of these two layers ensures stable wafer fixation while reducing micro-displacement during polishing, thereby improving wafer thickness uniformity. More preferably, the gradient hole structure of the present invention is a continuous conical hole, a stacked stepped hole, or a discontinuous foamed gradient hole.
[0009] Specifically, the gradient hole structure is a continuous conical hole, with a single hole continuously expanding from the micropore layer to the macropore layer. The negative pressure is conducted along the conical channel in a gradient decreasing manner, resulting in low airflow resistance and high uniformity of negative pressure distribution.
[0010] Specifically, the gradient pore structure is a stacked stepped pore structure, composed of at least two layers of porous materials with different pore sizes, and the pore size between layers changes in a stepped manner. This structure has a mature manufacturing process, and the pore size distribution can be precisely controlled by adjusting the amount of foaming agent in each layer and process parameters.
[0011] Specifically, the gradient pore structure is a discontinuous foamed gradient pore structure, where each pore does not penetrate the entire thickness of the adsorption pad, and the pore continuously expands from the microporous layer to the macroporous layer. This structure can be achieved through a one-step foaming process, eliminating the need for multi-layer composite processes, and the pore size transition is smooth.
[0012] More preferably, the average pore size of the microporous layer is 5-30 μm and the porosity is 30-60%; the average pore size of the macroporous layer is 50-200 μm and the porosity is 50-80%.
[0013] If the pore size of the microporous layer is too small, negative pressure conduction will be difficult; if it is too large, the adsorption force will be uneven. If the pore size of the macroporous layer is too small, it will not be able to effectively reduce flow resistance; if it is too large, the pad strength will be insufficient. The above parameter range takes into account both adsorption uniformity and structural strength.
[0014] More preferably, a mesoporous layer is further included between the microporous layer and the macroporous layer, and the average pore size of the mesoporous layer is 30-50 μm.
[0015] By adopting the above scheme, the mesoporous layer serves as a transition layer, mitigating the abrupt change in pore size between the microporous layer and the macroporous layer, improving the interlayer stress distribution, and avoiding fluctuations in adsorption force caused by negative pressure directly impacting the surface micropores from the bottom macropores.
[0016] More preferably, the thickness of the adsorption pad is 0.5-3 mm, the thickness of the microporous layer accounts for 20-40% of the total thickness of the adsorption pad, and the thickness of the macroporous layer accounts for 30-75% of the total thickness of the adsorption pad.
[0017] If the microporous layer is too thin, the effective support of the adsorption surface will be insufficient; if it is too thick, the resistance to negative pressure conduction will increase. If the macroporous layer is too thin, the negative pressure conduction efficiency will be limited; if it is too thick, the support rigidity of the wafer contact side will decrease.
[0018] More preferably, the absorbent pad is made of at least one of thermoplastic polyurethane elastomer, silicone rubber, fluororubber, and ethylene-vinyl acetate copolymer.
[0019] The above materials have good elastic resilience and foamability, which can meet the requirements of CMP process for pad wear resistance and chemical corrosion resistance.
[0020] Secondly, the present invention also provides a method for preparing the above-mentioned wax-free adsorption pad. Depending on the different types of gradient pore structures, the preparation method includes a laminated hot-pressing composite process, a gradient foaming one-step molding process, and a 3D printing molding process.
[0021] When the gradient pore structure is a stacked stepped pore, the preparation method includes: preparing a microporous layer foam material and a macroporous layer foam material respectively; and stacking the microporous layer foam material and the macroporous layer foam material to obtain a wax-free adsorption pad with a gradient pore structure.
[0022] Preferably, the microporous layer foaming material uses a physical foaming agent or a chemical foaming agent, and the amount of foaming agent is 0.5-3 wt% of the substrate mass; the macroporous layer foaming material uses the same or different foaming agents, and the amount of foaming agent is 3-10 wt% of the substrate mass.
[0023] Preferably, the laminated composite is produced using a hot-pressing process, with a hot-pressing temperature of 80-150℃, a hot-pressing pressure of 0.5-5MPa, and a hot-pressing time of 5-30min. By controlling the amount of foaming agent in each layer and the hot-pressing parameters, a stepwise change in the interlayer pore size can be achieved.
[0024] When the gradient hole structure is a discontinuous foamed gradient hole, the preparation method includes: controlling the concentration gradient distribution of the foaming agent in the mold, so that the foaming agent concentration on the wafer contact side is lower than the foaming agent concentration on the negative pressure access side, and foaming and molding in one step to obtain a wax-free adsorption pad with a discontinuous foamed gradient hole structure.
[0025] Preferably, the amount of surface foaming agent is 1wt% to 2wt% of the substrate mass, and the amount of bottom foaming agent is 4wt% to 7wt% of the substrate mass. This process eliminates the need for multi-layer lamination, simplifies the production process, and results in a smoother transition in pore size.
[0026] When the gradient hole structure is a continuous tapered hole, the fabrication method includes: using a photocurable resin or thermoplastic material as a substrate, and printing a tapered hole structure with gradually changing hole diameter layer by layer in the thickness direction using a multi-nozzle 3D printing device, with each hole continuously expanding from the wafer contact side to the negative pressure access side. This process can precisely control the hole shape and the gradient of hole diameter change, and is suitable for high-precision, small-batch customized needs.
[0027] In summary, the present invention has the following beneficial effects: (1) By using a gradient pore structure with gradually increasing pore size along the thickness direction, the functions of uniform adsorption of surface micropores and efficient negative pressure conduction of bottom macropores are realized, which significantly improves the fixation stability of the wafer during the polishing process, reduces the micro-displacement of the wafer caused by uneven adsorption, and thus improves the uniformity of wafer thickness. (2) By setting a mesoporous layer as a transition, the abrupt change in pore size between the microporous layer and the macroporous layer is alleviated, the uniformity of negative pressure distribution is further improved, and the risk of interlayer peeling is reduced. (3) The layered stepped pore structure adopts a mature foaming-hot pressing composite process, which is easy to industrialize and the pore size distribution can be precisely controlled by adjusting the amount of foaming agent in each layer; the discontinuous foaming gradient pore structure is achieved by one-step foaming molding, without the need for multi-layer composite, which simplifies the process and reduces production costs; the continuous conical pore structure is formed by 3D printing, with smooth and continuous pores, minimal negative pressure conduction resistance, and the shortest adsorption response time, making it suitable for ultra-high precision application scenarios. Attached Figure Description
[0028] Figure 1 This is a schematic cross-sectional view of the wax-free adsorption pad with a layered stepped pore structure in Example 1; Figure 2 This is a schematic cross-sectional view of the wax-free adsorption pad with a discontinuous foamed gradient pore structure in Example 2; Figure 3 This is a schematic cross-sectional view of the wax-free adsorption pad with a continuous conical hole structure in Example 3; Figure 4 This is a schematic diagram of the cross-section of the wax-free adsorption pad with a uniform pore structure in Comparative Example 1. Detailed Implementation
[0029] The following specific examples illustrate the implementation of the present invention. Those skilled in the art can easily understand other advantages and effects of the present invention from the content disclosed in this specification. The present invention can also be implemented or applied through other different specific embodiments, and various details in this specification can also be modified or changed based on different viewpoints and applications without departing from the spirit of the present invention.
[0030] Furthermore, it should be understood that the one or more method steps mentioned in this invention do not preclude the existence of other method steps before or after the combined steps, or the insertion of other method steps between these explicitly mentioned steps, unless otherwise stated. Moreover, unless otherwise stated, the numbering of each method step is merely a convenient tool for identifying each method step, and not intended to limit the order of the method steps or limit the scope of the invention. Changes or adjustments to their relative relationships, without substantially altering the technical content, should also be considered within the scope of the invention.
[0031] Unless otherwise specified, the experimental conditions used in the examples are generally in accordance with conventional conditions in the art or the conditions recommended by the reagent company. Unless otherwise specified, the materials and reagents used in the examples can be purchased commercially.
[0032] Test methods 1. Average pore size and porosity (1) Average aperture The liquid nitrogen brittle fracture section of each layer of foamed sheet was observed using a scanning electron microscope (SEM). At least five fields of view were randomly selected at 500× and 2000× magnification, and the cell diameter was measured using image analysis software. The arithmetic mean was taken as the average cell diameter.
[0033] (2) Porosity According to GB / T 6343-2009 "Determination of Apparent Density of Foamed Plastics and Rubber", the apparent density of each layer of foamed sheet was determined by the dimensional method: Cut a regular rectangular sample (not less than 50mm × 50mm × the original thickness of the layer), measure the thickness at the four corners and center of the sample with a vernier caliper, and take the average value of 5 points; measure the length and width with a ruler; calculate the apparent volume V = length × width × thickness, and the apparent density ρapparent = m / V (m is the mass of the sample).
[0034] Porosity is calculated using the formula: Porosity = (1 - ρapparent / ρsolid) × 100%.
[0035] The solid density of each substrate was measured using GB / T 1033.1-2008 for unfoamed substrates.
[0036] 2. Total Thickness Change (TTV) A standard silicon wafer was adsorbed onto the test pad and run under simulated CMP conditions: 60 rpm, polishing pressure 2 psi, polishing slurry flow rate 200 mL / min, and running time 30 min. The thickness was measured using the non-contact scanning method in GB / T 6618-2023 "Test Method for Thickness and Total Thickness Variation of Silicon Wafers". The difference between the maximum and minimum thickness was calculated as TTV.
[0037] 3. Service life The CMP polishing simulation cycle test method was used. Adsorption pads were mounted on the polishing apparatus, and a standard silicon wafer was subjected to repeated adsorption-polishing-release cycles. Each cycle included four stages: adsorption, polishing, cleaning, and release. Failure was defined as the wafer's total volumetric TV (TTV) exceeding 5 μm or the adsorption pad surface exhibiting any of the following: collapse, cracks, or delamination. The cumulative number of cycles recorded was the lifetime of the wafer.
[0038] Example Example 1 This embodiment provides a wax-free adsorption pad with a layered stepped pore structure, which is prepared by using thermoplastic polyurethane elastomer (TPU) as the substrate and through a multilayer hot-pressing composite process.
[0039] The total thickness of the adsorption pad is 1.5 mm, and it is composed of three layers: a microporous layer, a mesoporous layer, and a macroporous layer. For example... Figure 1 As shown, the adsorption pad has a gradient pore structure with progressively increasing pore size along its thickness direction. The wafer contact side is a microporous layer, and the negative pressure access side is a macroporous layer. The layers are bonded together by a thermo-pressed composite interface. Wherein: Microporous layer: 0.3 mm thick, with an average pore size of about 15 μm and a porosity of about 45%, located on the wafer contact side; Mesoporous layer: 0.4 mm thick, with an average pore size of about 35 μm and a porosity of about 55%; located between the microporous layer and the macroporous layer; Macroporous layer: 0.8 mm thick, with an average pore size of about 80 μm and a porosity of about 70%, located on the negative pressure access side.
[0040] Preparation method: S1: Prepare three-layer foamed sheets. The microporous layer is made by blending TPU particles with 0.8 wt% azodicarbonamide foaming agent and molding and foaming at 160℃ and 5MPa. The mesoporous layer is made by blending TPU particles with 2.5 wt% azodicarbonamide foaming agent and molding and foaming at 160℃ and 3MPa. The macroporous layer is made by blending TPU particles with 5 wt% azodicarbonamide foaming agent and adding 0.5 wt% nano-silica as a cell stabilizer, and molding and foaming at 160℃ and 2MPa.
[0041] S2: Stack the three-layer foamed sheets in the order of microporous layer / mesoporous layer / macroporous layer, and hot press them in a hot press at 120℃ and 2MPa for 15 minutes. After cooling, cut them into the required size to obtain a wax-free adsorption pad.
[0042] Comparative Example 1 This comparative example provides a wax-free adsorption pad with a uniform pore structure, which is prepared by using thermoplastic polyurethane elastomer as the substrate and through a multilayer hot-pressing composite process.
[0043] To eliminate the influence of the multilayer composite process itself on the performance of the adsorption pad, this comparative example uses the same multilayer composite process as Example 1, but the pore size and porosity of each layer are the same. Figure 4 As shown, the pore size and porosity of each layer in the adsorption pad are uniform along the thickness direction, with no pore size gradient distribution. The total thickness of the adsorption pad is 1.5 mm, and it is composed of three microporous layers of different thicknesses but the same pore size. The dimensional parameters of the three microporous layers are as follows: Microporous layer 1: 0.3 mm thick, with an average pore size of about 15 μm and a porosity of about 45%, located on the wafer contact side; Microporous layer 2: 0.4 mm thick, with an average pore size of about 15 μm and a porosity of about 45%; located between microporous layer 1 and microporous layer 3; Microporous layer 3: 0.8 mm thick, with an average pore size of about 15 μm and a porosity of about 45%, located on the negative pressure access side.
[0044] Preparation method: S1: Prepare three-layer foamed sheets. Microporous layer 1, microporous layer 2, and microporous layer 3 are all made by blending TPU particles with 0.8wt% azodicarbonamide foaming agent and molding and foaming at 160℃ and 5MPa. By controlling the amount of TPU added, sheets with thicknesses of 0.3mm, 0.4mm, and 0.8mm are obtained, respectively.
[0045] S2: Stack the three-layer foamed sheets in the order of microporous layer 1 / microporous layer 2 / microporous layer 3, and hot press them together in a hot press at 120℃ and 2MPa for 15 minutes. After cooling, cut them into the required size to obtain a wax-free adsorption pad.
[0046] Comparative Example 2 This comparative example provides a wax-free adsorption pad with a uniform pore structure, which is prepared by using thermoplastic polyurethane elastomer as the substrate and through a multilayer hot-pressing composite process.
[0047] To eliminate the influence of the multilayer composite process itself on the performance of the adsorption pad, this comparative example uses the same multilayer composite process as Example 1, but with the same pore size and porosity for each layer. The total thickness of the adsorption pad is 1.5 mm, composed of three mesoporous layers of different thicknesses but the same pore size. The dimensional parameters of the three mesoporous layers are as follows: Mesopore layer 1: 0.3 mm thick, with an average pore diameter of about 35 μm and a porosity of about 55%, located on the wafer contact side; Mesoporous layer 2: 0.4 mm thick, with an average pore size of about 35 μm and a porosity of about 55%; located between mesoporous layer 1 and mesoporous layer 3; Mesoporous layer 3: 0.8 mm thick, with an average pore size of about 35 μm and a porosity of about 55%, located on the negative pressure access side.
[0048] Preparation method: S1: Prepare three-layer foamed sheets. Mesoporous layer 1, mesoporous layer 2, and mesoporous layer 3 are all made by blending TPU particles with 2.5wt% azodicarbonamide foaming agent and molding and foaming at 160℃ and 3MPa. By controlling the amount of TPU added, sheets with thicknesses of 0.3mm, 0.4mm, and 0.8mm were obtained, respectively.
[0049] S2: Stack the three-layer foamed sheets in the order of mesoporous layer 1 / mesoporous layer 2 / mesoporous layer 3, and hot press them together in a hot press at 120℃ and 2MPa for 15 minutes. After cooling, cut them into the required size to obtain a wax-free adsorption pad.
[0050] Comparative Example 3 This comparative example provides a wax-free adsorption pad with a uniform pore structure, which is prepared by using thermoplastic polyurethane elastomer as the substrate and through a multilayer hot-pressing composite process.
[0051] To eliminate the influence of the multilayer composite process itself on the performance of the adsorption pad, this comparative example uses the same multilayer composite process as Example 1, but with the same pore size and porosity for each layer. The total thickness of the adsorption pad is 1.5 mm, composed of three macroporous layers of different thicknesses but the same pore size. The dimensional parameters of the three macroporous layers are as follows: Macropore layer 1: 0.3 mm thick, with an average pore diameter of about 80 μm and a porosity of about 70%, located on the wafer contact side; Macroporous layer 2: 0.4 mm thick, with an average pore size of about 80 μm and a porosity of about 70%; located between macroporous layer 1 and macroporous layer 3; Macroporous layer 3: 0.8 mm thick, with an average pore size of about 80 μm and a porosity of about 70%, located on the negative pressure access side.
[0052] Preparation method: S1: Three-layer foamed sheets were prepared separately. Macroporous layer 1, macroporous layer 2, and macroporous layer 3 were all made by blending TPU particles with 5 wt% azodicarbonamide foaming agent and adding 0.5 wt% nano-silica as a cell stabilizer. The foaming was carried out by compression molding at 160℃ and 2MPa. The amount of TPU added was controlled to obtain sheets with thicknesses of 0.3 mm, 0.4 mm, and 0.8 mm, respectively.
[0053] S2: Stack the three-layer foamed sheets in the order of macroporous layer 1 / macroporous layer 2 / macroporous layer 3, and hot press them together in a hot press at 120℃ and 2MPa for 15 minutes. After cooling, cut them into the required size to obtain a wax-free adsorption pad.
[0054] Test Results The size and performance of the wax-free adsorption pads prepared in Example 1 and Comparative Examples 1-3 were tested. The test results are shown in Table 1 and Table 2.
[0055] Table 1. Test results of average pore size and porosity of each layer in Example 1 and Comparative Examples 1-3 Table 2. TTV test results of Example 1 and Comparative Examples 1-3 Results analysis: (1) The measured average pore sizes of the microporous layer, mesoporous layer and macroporous layer in Example 1 were 14.2 μm, 33.5 μm and 78.6 μm, respectively, and the measured porosities were 43.5%, 53.8% and 68.5%, respectively. Compared with the control target values (15 μm, 35 μm, 80 μm and 45%, 55% and 70%) in the preparation process, the deviations were all within the normal process fluctuation range of ±10%, which proves the controllability and repeatability of the stacked stepped pore structure.
[0056] (2) The TTV of Example 1 is 1.5μm, which is far below the failure threshold of 5μm; the service life reaches 851 times, and it eventually fails due to slight surface collapse rather than TTV exceeding the standard, proving that the gradient hole structure maintains the uniformity of wafer thickness during long-term use.
[0057] (3) Comparative Example 1 (all micropores) and Comparative Example 3 (all macropores) exceeded 5 μm in TTV after the first 30 min simulated CMP test. This is because the airflow resistance of the micropore layer is too large, resulting in severe attenuation of negative pressure from the vacuum disk to the wafer contact surface, insufficient adsorption force at the wafer edge, and local deformation. The actual contact area between the macropore layer and the wafer is too small, and local stress concentration leads to severe deterioration of wafer thickness uniformity. Although the initial TTV of Comparative Example 2 (all mesopores) did not exceed 5 μm, it gradually deteriorated to exceed 5 μm during the cyclic test and failed after 482 cycles. The above results prove that uniform micropore structure, uniform mesopore structure, and uniform macropore structure cannot meet the requirements of precise wafer thickness control, demonstrating the advantages of gradient hole structure.
[0058] Example 2 This embodiment provides a wax-free adsorption pad with a discontinuous foamed gradient pore structure, which is made of silicone rubber as the substrate and prepared by a gradient foaming one-step molding process.
[0059] The discontinuous foaming gradient pore refers to a pore structure in which the concentration of the foaming agent is distributed in a discontinuous stepwise manner along the thickness direction, resulting in a gradient change in pore size after foaming and the pores are not completely interconnected.
[0060] The total thickness of the absorbent pad is 2mm. It is formed through one-step vulcanization and foaming by controlling the concentration gradient distribution of the foaming agent within the mold. For example... Figure 2 As shown, the adsorption pad has a gradient pore structure with continuously varying pore size along the thickness direction, without interlayer physical interfaces. The pore size is smallest on the wafer contact side and largest on the negative pressure access side. Wherein: Microporous layer: thickness controlled at 0.5 mm, average pore size of about 10 μm, porosity of about 40%, located on the wafer contact side; Mesoporous layer: thickness controlled at 0.7 mm, average pore size approximately 40 μm, porosity approximately 55%; located between the microporous layer and the macroporous layer; Macroporous layer: thickness controlled at 0.8 mm, average pore diameter of about 100 μm, porosity of about 75%, located on the negative pressure access side.
[0061] Preparation method: Liquid silicone rubber is mixed with different amounts of chemical foaming agent and injected into the mold in layers. The amount of foaming agent in the surface layer is 1 wt%, the amount of foaming agent in the bottom layer is 6 wt%, and the amount of foaming agent in the middle layer is 3 wt%. The mixture is vulcanized and foamed at 150℃ for 20 min, and a wax-free adsorption pad is obtained by one-step molding.
[0062] The average pore size, porosity, TTV and service life of the wax-free adsorption pad prepared in Example 2 were tested.
[0063] The average pore size and porosity test results showed that after layering and cutting along the thickness direction, the average pore size of the micropore region was 9.8 μm, and the porosity was 39.2%; the average pore size of the mesopore region was 38.5 μm, and the porosity was 54.5%; and the average pore size of the macropore region was 97.2 μm, and the porosity was 74.8%. The measured values for each region were within the normal process fluctuation range compared to the control target values (10 μm, 40 μm, 100 μm and 40%, 55%, 75%) during the preparation process. This demonstrates that the gradient change in pore size can be achieved by controlling the gradient distribution of the foaming agent concentration in the discontinuous foaming gradient pore structure.
[0064] The TTV test results show that the TTV of Example 2 is 1.6μm, which does not exceed the failure threshold of 5μm.
[0065] The service life test results showed that the service life of Example 2 was 922 cycles, and it eventually failed due to slight surface collapse. During the test, the TTV never exceeded 5μm.
[0066] The above results show that the discontinuous foamed gradient pore structure can achieve the same technical effect as the stacked stepped pore structure through one-step foaming molding, without the need for multiple composite processes, thus simplifying the production process.
[0067] Example 3 This embodiment provides a wax-free adsorption pad with a continuous conical pore structure, which is prepared by 3D printing (direct writing molding) process.
[0068] Using photocurable polyurethane resin as a substrate, a tapered hole structure with continuously varying apertures is printed layer by layer in the thickness direction using a multi-nozzle 3D printing device. For example... Figure 3 As shown, the adsorption pad has a continuous tapered channel running along the thickness direction. Each pore expands continuously from the wafer contact side to the negative pressure access side, and the pore walls are smooth with no interlayer interface. The opening diameter of the surface pore is about 20 μm, and the opening diameter of the bottom pore is about 120 μm. Each pore is a continuous tapered pore that runs through the entire thickness (1 mm) of the adsorption pad.
[0069] The average pore size, porosity, TTV and service life of the wax-free adsorption pad prepared in Example 3 were tested.
[0070] Average pore size and porosity test results show that, using micro-CT scanning combined with image analysis, the pore size of the wax-free adsorption pad continuously increases from the surface to the bottom layer along the thickness direction, exhibiting a continuous conical gradient characteristic, consistent with the 3D printing design parameters. Layered sampling tests revealed an average porosity of approximately 52% in the surface 0.3mm region and approximately 68% in the bottom 0.7mm region.
[0071] The TTV test results show that the TTV of Example 3 is 1.2 μm, the lowest among all examples, and does not exceed the failure threshold of 5 μm. This result indicates that the continuous tapered channel is smooth and continuous, without interlayer interfaces, and has the most uniform negative pressure conduction, resulting in the most precise control over wafer thickness.
[0072] The service life test results showed that the service life of Example 3 was 780 cycles, and it eventually failed due to surface microcracks. During the test, the TTV never exceeded 5μm.
[0073] The above results show that the continuous conical hole structure can achieve precise control of the channel through 3D printing, which is suitable for ultra-high precision application scenarios.
[0074] Example 4 This embodiment provides a wax-free adsorption pad with a layered stepped pore structure, which is prepared by using thermoplastic polyurethane elastomer as the substrate and through a multilayer hot-pressing composite process.
[0075] The difference between this embodiment and Embodiment 1 is that the adsorption pad is composed of only two layers: a microporous layer and a macroporous layer, without a mesoporous layer, and the total thickness is 0.8 mm.
[0076] The specific structural parameters of the adsorption pad are as follows: Microporous layer: 0.2 mm thick (accounting for 25% of the total thickness), with an average pore size of about 12 μm and a porosity of about 50%, located on the wafer contact side; Macroporous layer: 0.6 mm thick (accounting for 75% of the total thickness), with an average pore size of about 150 μm and a porosity of about 65%, located on the negative pressure access side.
[0077] Preparation method: S1: Two layers of foamed sheets were prepared separately. The microporous layer was made by blending TPU particles with 0.6 wt% azodicarbonamide foaming agent and molding and foaming at 160℃ and 5MPa. The macroporous layer was made by blending TPU particles with 6 wt% azodicarbonamide foaming agent and adding 0.5 wt% nano-silica as a cell stabilizer and molding and foaming at 160℃ and 1.5MPa.
[0078] S2: Stack two layers of foamed sheets in the order of microporous layer / macroporous layer, and hot press them together in a hot press at 120℃ and 2MPa for 15 minutes. After cooling, cut them into the required size to obtain a wax-free adsorption pad.
[0079] Example 5 This embodiment provides a wax-free adsorption pad with a layered stepped pore structure, which is prepared by using fluororubber (FKM, vinylidene fluoride-hexafluoropropylene copolymer) as the substrate and through a multilayer hot-pressing composite process.
[0080] The difference between this embodiment and Embodiment 1 is that the substrate is made of fluororubber and the total thickness is 2.5mm.
[0081] The specific structural parameters of the adsorption pad are as follows: Microporous layer: 0.8 mm thick (accounting for 32% of the total thickness), with an average pore size of about 25 μm and a porosity of about 55%, located on the wafer contact side; Mesoporous layer: 0.5 mm thick (accounting for 20% of the total thickness), with an average pore size of about 45 μm and a porosity of about 60%, located between the microporous layer and the macroporous layer; Macroporous layer: 1.2 mm thick (accounting for 48% of the total thickness), with an average pore size of about 180 μm and a porosity of about 78%, located on the negative pressure access side.
[0082] Preparation method: S1: Prepare three-layer foamed sheets. The microporous layer is made by blending fluororubber raw material with 1.5 wt% azodicarbonamide foaming agent and molding and foaming at 170℃ and 6MPa; the mesoporous layer is made by blending fluororubber raw material with 3.5 wt% azodicarbonamide foaming agent and molding and foaming at 170℃ and 4MPa; the macroporous layer is made by blending fluororubber raw material with 7 wt% azodicarbonamide foaming agent and adding 0.5 wt% nano-silica as a cell stabilizer and molding and foaming at 170℃ and 2MPa.
[0083] S2: Stack the three-layer foamed sheets in the order of microporous layer / mesoporous layer / macroporous layer, and hot press them in a hot press at 130℃ and 2.5MPa for 20 minutes. After cooling, cut them into the required size to obtain a wax-free adsorption pad.
[0084] Example 6 This embodiment provides a wax-free adsorption pad with a multilayered stepped pore structure, which is prepared by using ethylene-vinyl acetate copolymer (EVA, VA content 18%) as the substrate and through a multilayer hot-pressing composite process.
[0085] The difference between this embodiment and Embodiment 1 is that the substrate is EVA and the total thickness is 1.2mm.
[0086] The specific structural parameters of the adsorption pad are as follows: Microporous layer: 0.3 mm thick (accounting for 25% of the total thickness), with an average pore size of about 18 μm and a porosity of about 48%, located on the wafer contact side; Macroporous layer: 0.9 mm thick (accounting for 75% of the total thickness), with an average pore size of about 120 μm and a porosity of about 68%, located on the negative pressure access side.
[0087] Preparation method: S1: Two layers of foamed sheets were prepared separately. The microporous layer was made by blending EVA particles with 1.0 wt% azodicarbonamide foaming agent and molding and foaming at 150℃ and 4MPa. The macroporous layer was made by blending EVA particles with 4.5 wt% azodicarbonamide foaming agent and molding and foaming at 150℃ and 2MPa.
[0088] S2: Stack two layers of foamed sheets in the order of microporous layer / macroporous layer, and hot press them together in a hot press at 110℃ and 1.5MPa for 12 minutes. After cooling, cut them into the required size to obtain a wax-free adsorption pad.
[0089] Example 7 This embodiment provides a wax-free adsorption pad with a discontinuous foamed gradient pore structure, which is made of silicone rubber (MVQ) as the substrate and prepared by a gradient foaming one-step molding process.
[0090] The difference between this embodiment and Embodiment 2 is that the adsorption pad consists of only two pore sizes: a microporous area and a macroporous area, without a mesoporous area, and the total thickness is 1.5 mm.
[0091] The specific structural parameters of the adsorption pad are as follows: Micropore region: approximately 0.4 mm thick (accounting for 27% of the total thickness), with an average pore diameter of approximately 15 μm and a porosity of approximately 42%, located on the wafer contact side; Large pore area: approximately 1.1 mm thick (accounting for 73% of the total thickness), with an average pore diameter of approximately 90 μm and a porosity of approximately 72%, located on the negative pressure inlet side.
[0092] Preparation method: S1: Mix 100 parts of liquid silicone rubber (vinyl content 0.15%), 25 parts of fumed silica, 4 parts of hydroxyl silicone oil, and 0.4 parts of platinum catalyst evenly in a vacuum kneader to obtain a compound.
[0093] S2: Divide the rubber compound into two portions and add different amounts of azodicarbonamide foaming agent to each: add 1.2 wt% foaming agent to the microporous area and 5.0 wt% foaming agent to the macroporous area. Inject the two portions of rubber compound into a mold (mold depth 1.5 mm) in sequence, and vulcanize and foam at 150℃ and 4 MPa for 18 min to obtain a wax-free adsorption pad with a discontinuous foamed gradient pore structure in one step.
[0094] Test Results The wax-free adsorption pads prepared in Examples 4-7 were subjected to TTV and service life tests. The test results are shown in Table 3.
[0095] Table 3. Test results of TTV and service life in Examples 4-7 The test results in Table 3 show that: (1) Example 4 is a composite of two layers, a microporous layer and a macroporous layer, without a mesoporous layer. Its TTV is 1.7μm and its service life is 766 cycles, which are significantly better than the comparative example. This proves that even without a mesoporous transition layer, the two-layer gradient structure of only the microporous layer and the macroporous layer can still achieve the technical effect of the present invention.
[0096] (2) The TTV of Example 5 is 1.8 μm and the service life is 974 cycles, which is the longest service life among all examples. This is due to the excellent high temperature resistance and chemical corrosion resistance of fluororubber, which is suitable for harsh CMP process environments.
[0097] (3) Example 6 uses EVA material, which is a two-layer composite with a TTV of 1.5μm and a service life of 723 cycles. It eventually fails due to interlayer delamination, but the TTV never exceeds 5μm during the test.
[0098] (4) Example 7 is a discontinuous foamed gradient pore structure with only two pore diameter regions: micropore region and macropore region, without mesopore region. Its TTV is 1.6μm and its service life is 889 cycles, which are significantly better than the comparative example. This proves that even without setting a mesopore transition region, the discontinuous foamed gradient pore structure can still achieve the technical effect of the present invention by only using the gradient combination of micropore region and macropore region.
[0099] The above description is merely a preferred embodiment of the present invention and is not intended to limit the present invention in any form or substance. It should be noted that those skilled in the art can make various improvements and additions without departing from the method of the present invention, and these improvements and additions should also be considered within the scope of protection of the present invention. Any modifications, alterations, and equivalent changes made by those skilled in the art based on the above-disclosed technical content without departing from the spirit and scope of the present invention are equivalent embodiments of the present invention. Furthermore, any modifications, alterations, and evolutions made to the above embodiments based on the essential technology of the present invention still fall within the scope of the technical solution of the present invention.
Claims
1. A wax-free adsorption pad with a gradient pore structure, characterized in that, The device has a gradient pore structure with increasing pore size along the thickness direction. The gradient pore structure includes a microporous layer located on the wafer contact side and a macroporous layer located on the negative pressure access side. The average pore size of the microporous layer is 5-30 μm and the porosity is 30-60%. The average pore size of the macroporous layer is 50-200 μm and the porosity is 50-80%.
2. The wax-free absorbent pad according to claim 1, characterized in that, The gradient pore structure is a continuous conical pore, a stacked stepped pore composed of at least two layers of porous materials with different pore sizes, or a discontinuous foamed gradient pore.
3. The wax-free absorbent pad according to claim 1, characterized in that, The thickness of the adsorption pad is 0.5-3.0 mm, the thickness of the microporous layer accounts for 20-40% of the total thickness of the adsorption pad, and the thickness of the macroporous layer accounts for 30-75% of the total thickness of the adsorption pad.
4. The wax-free absorbent pad according to claim 2, characterized in that, The gradient pore structure is a stacked stepped pore structure, and a mesopore layer is also included between the micropore layer and the macropore layer. The average pore size of the mesopore layer is 30-50 μm.
5. The wax-free absorbent pad according to claim 4, characterized in that, The thickness of the mesoporous layer accounts for 10-30% of the total thickness of the adsorption pad.
6. The wax-free absorbent pad according to claim 1, characterized in that, The absorbent pad is made of at least one of thermoplastic polyurethane elastomer, silicone rubber, fluororubber, or ethylene-vinyl acetate copolymer.
7. A method for preparing the wax-free adsorption pad according to claim 2 or 4, characterized in that, The gradient pore structure is a stacked stepped pore structure. The specific preparation steps are as follows: S1, prepare microporous layer foam material and macroporous layer foam material respectively; S2, stack the microporous layer foam material and the macroporous layer foam material, and cut them to obtain a wax-free adsorption pad.
8. The preparation method according to claim 7, characterized in that, Step S1 further includes preparing a mesoporous layer foam material, and in step S2, a three-layer composite is performed in the order of microporous layer / mesoporous layer / macroporous layer.
9. A method for preparing the wax-free adsorption pad according to claim 2, characterized in that, The gradient hole structure is a discontinuous foamed gradient hole. The specific preparation steps are as follows: control the concentration gradient distribution of the foaming agent in the mold so that the foaming agent concentration on the wafer contact side is lower than the foaming agent concentration on the negative pressure access side, and foam in one step to obtain a wax-free adsorption pad.
10. A method for preparing the wax-free adsorption pad according to claim 2, characterized in that, The gradient hole structure is a continuous conical hole. The specific preparation steps are as follows: using photocurable resin or thermoplastic material as the substrate, a conical hole structure with gradually changing hole diameter is printed layer by layer in the thickness direction through a multi-nozzle 3D printing device to obtain a wax-free adsorption pad.
Citation Information
Patent Citations
A wafer single-sided polishing apparatus and method
CN115056045B
No wax polishing adsorption pad pastes device
CN207757470U